Fill Me App: An Interactive Mobile Game Application for Children with Autism - Eder, Marylene Saldon; L. Diaz, John Maruel; S. Madela, Joanne Ruth; U. Mag-usara, Marife; M. Sabellano, Dhally Dith (International Journal of Interactive Mobile Technologies (iJIM), 2016)
FillMeApp is an interactive mobile game application which is a supplementary learning material intended for children with Autism that helps them motivate in their learning process. This game application is focus mainly on Science basically on identifying the human’s body parts. Accumulating the best time for focus monitoring, eye-catching graphics, simple level of exercises, video tutorial and background music that coincide with the current educational teachings are among the primary features that this application has to offer. The researchers analyzed the results of the test survey and proved that the application is user friendly, interactive, the logic of the game is understandable and would learn to use this application very useful in their learning. Based also from the researchers testing and result on the students motivational rating from the teacher, before, the students with Autisms’ motivation level were LOW but after the game application was deployed and tested their motivation status begin to grow and become HIGH.